Gender disparity in care-seeking behaviours and treatment outcomes for dehydrating diarrhoea among under-5 children admitted to a diarrhoeal disease hospital in Bangladesh: an analysis of hospital-based surveillance data - Subhasish Das; Tahmeed Ahmed; Imteaz Mahmud; Soroar Hossain Khan; A S G Faruque (BMJ Open)
Introduction Despite economic development and augmented literacy rates, Bangladeshi households are still discriminating against girls when it comes to seeking medical care. We examined gender disparities in diarrhoeal disease severity and the treatment outcomes of under-5 children.Setting A tertiary level diarrhoeal disease hospital in Dhaka, Bangladesh.Participants 13 361 under-5 children admitted to the hospital between January 2008 and December 2017.Outcome variables and methods The primary outcome of interest was severity of diarrhoea, defined as ‘dehydrating diarrhoea’ or ‘non-dehydrating diarrhoea’. Multivariable logistic regression analyses were performed to assess the association between ‘gender’ and admission to hospital for dehydrating diarrhoea.Results Data on 13 321 children under 5 years of age were analysed, of whom 61.5% were male and 38.5% were female. The mean (±SD) age of children with diarrhoea was 5.63 (±3.49) months. The median distance travelled to come to the hospital for admission was 10 miles (IQR: 6–25) and was significantly higher for boys (10 miles, IQR: 6–25) than girls (9.5 miles, IQR: 6–23) (p<0.001). Girls had 1.11 times higher odds (adjusted OR: 1.11, 95% CI 1.03 to 1.20, p=0.007) of presenting with dehydrating diarrhoea than boys at the time of hospital admission. Almost 20% of children received two or more medications during the period of hospital admission and this did not differ by gender. The median duration of hospital stay was 11 hours and was similar in both sexes. No gender-based disparity was observed in the management of diarrhoea and in the hospital outcome of children.Conclusion We found that girls were more likely to have dehydrating diarrhoea when they were presented to the Dhaka hospital of International Centre for Diarrhoeal Disease Research, Bangladesh. No gender-based disparity was observed in the hospital outcome of children.